LITERATURE REVIEW: GREEN TEA EXTRACT POTENCY (Camellia sinensis) in LOWERING GLYCEMIC INDEX OF A WISTAR RAT - Filda Nisrina Fajrin; Imam Prabowo; Lisa Safira (Pharmacy Program, Faculty of Medicine, UPN Veteran Jakarta, 2022)
The aim of the research is to determine the potency of green tea extract (Camellia sinesis) to decrease blood glucose levels in diabetes mellitus model Wistar rats. A systematic review based on PRISMA-P 2020 with a literature search strategy using Google Scholar, PubMed, Science Direct, and Scopus databases. Literature quality was assessed using the JBI Critical Appraisal Checklist which produced 12 comprehensive potential literatures based on selection with inclusion and exclusion criteria. Analysis of 12 journals found that there were 11 studies that showed a significant decrease in blood glucose levels after administration of green tea extract (Camellia sinensis). Green tea extract (Camellia sinensis) has the potential to reduce blood glucose levels in Wistar strain rats with diabetes mellitus model. The mechanism underlying the antihyperglycemic effect is proven to be due to the protective and antidiabetic effects of the compounds contained in green tea extract, especially the flavonoid group, namely catechins. The minimum dose of green tea extract observed to cause an antihyperglycemic effect in experimental animals was 40 mg/kgBW.